2020
DOI: 10.1186/s13075-020-02348-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porphyromonas gingivalis infection on gut dysbiosis and resultant arthritis exacerbation in mouse model

Abstract: Background Porphyromonas gingivalis (Pg) infection causes periodontal disease and exacerbates rheumatoid arthritis (RA). It is reported that inoculation of periodontopathogenic bacteria (i.e., Pg) can alter gut microbiota composition in the animal models. Gut microbiota dysbiosis in human has shown strong associations with systemic diseases, including RA, diabetes mellitus, and inflammatory bowel disease. Therefore, this study investigated dysbiosis-mediated arthritis by Pg oral inoculation in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 62 publications
0
49
0
Order By: Relevance
“…Indeed, timing may play a role here as previous publications demonstrating an exacerbation of arthritis through periodontal disease opted for shorter time lapses between inductions of both diseases [ 37 39 ]. More differences may arise from the use of various mouse strains, different modes to induce arthritis to the point of collagen type II derived from chicken vs cow [ 29 , 40 ]. In our experiments, the sums of arthritis scores at endpoint were higher for those mice that were subjected to CIA first however, we attribute this difference to different disease durations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, timing may play a role here as previous publications demonstrating an exacerbation of arthritis through periodontal disease opted for shorter time lapses between inductions of both diseases [ 37 39 ]. More differences may arise from the use of various mouse strains, different modes to induce arthritis to the point of collagen type II derived from chicken vs cow [ 29 , 40 ]. In our experiments, the sums of arthritis scores at endpoint were higher for those mice that were subjected to CIA first however, we attribute this difference to different disease durations.…”
Section: Discussionmentioning
confidence: 99%
“…Oral microbiota seems to have a crucial role not only in RA pathogenesis but also in exacerbation of joint involvement and in treatment response. In fact, it has been shown that dysbiosis may exacerbate arthritis through the oral inoculation of P. gingvalis using animal models, even if the mechanism underlying the exacerbation is not entirely elucidated [ 49 ]. In a collagen-type II experimental arthritis in mice, periodontitis caused by P. gingivalis and Provotellanigrescens exacerbated arthritis through TLR2-dependent antigen-specific Th17 immune response [ 49 ].…”
Section: Oral Microbiome and Rheumatoid Arthritismentioning
confidence: 99%
“…Therefore, it is questioned whether PPAD synthesized by P. gingivalis influences the progression of RA (129)(130)(131). A hypothesis was proposed that immune responses in the gut that were elicited with P. gingivalis inoculation exacerbated RA (132). T helper 17 (Th17) cells have been proven to be involved in the progression of RA by regulating the adaptive immune response, particularly at mucosal surfaces in the intestine (133).…”
Section: Effect Of P Gingivalis On Intestinal Immune Barriermentioning
confidence: 99%